ONE OF THE THREE: THE STATUS AND ROLE OF A SEIMAS’ SPEAKER - Trainauskienė, Sigita (Politologija, 2016)
The article analyses the role of a Parliament Speaker as a leader of one of the main institutions in representative democracy. The analysis is based on the premises of the theories of neoinstitutionalism and political leadership; the basic types of roles a speaker may have in different political systems are reviewed; and the established Lithuanian practice is studied accordingly. There are constitutional, statutory, traditional and ceremonial, procedural, and administrative functions and powers that are usually attributed to the Speaker, but the primary function of the presiding officer of a parliament is to conduct debates in parliament, to control its agenda as well as to represent the institution. While performing one’s tasks, the Speaker may be seen as a party asset as in the US Congress or a neutral chairman as in the UK House of Commons, however, neutrality by many scholars is seen as a basic feature attributed to this office. The studies conducted in the framework of institutionalisation of parliaments highlight several criteria inherent in highly-institutionalised legislatures such as professionalism of its leadership (i.e. long congressional career path) and “well-boundedness” of an institution (i.e. no lateral entry from outside), among other things. Scholars also highlight that it is not only formal powers but also subjective factors depending on a concrete personality that define the authority and the actual role the Speaker plays in the political process. The role of a Speaker of the Seimas is analysed based on theoretical criteria. After examination of the legal basis, status, formal powers of the Speaker of the Seimas as well as other factors, it is possible to conclude the following: The role of the presiding officer of the Parliament in Lithuania has changed since the beginning of the independence period due to changing constitutional arrangements, legal framework and political circumstances; despite the existence of collective bodies in the Seimas – the Board of the Seimas and the Conference of Chairs, at present Speaker of the Seimas is an individual leader. Although formally it is the second highest position in the hierarchy of state officers having mandate to substitute the head of the state, according to the established informal practice it is only the third official in terms of political power, being overshadowed by Prime Minister. That is why, it is only the “third choice” for politicians in their political career. Speaker of the Seimas can be described as a “party asset” type of a Speaker because of his/her relatively broad procedural powers and active political role played by the person despite the formal requirement to suspend one’s membership in the party group – there were several Speakers who retained their formal party leadership while in office. • A selection mechanism for the Office of the Speaker, i.e. inter-party negotiations for the governing coalition, is by far the most important informal variable defining the choice of the person and his/her behaviour later on while in office. Political conjuncture also stipulates relative instability of the Office and the change of Speaker without completing their full term (which is a rather seldom phenomena in Western parliaments). Party discipline and necessity to form a ruling coalition overrides even a secret ballot procedure in election of a Speaker thus diminishing the authority of an institution (the cases of re-voting for Arūnas Valinskas and a sudden replacement of Vydas Gedvilas by Loreta Graužinienė in the middle of their term). • Despite the weakness and instability of the party system in Lithuania, with “newcomers” in the Parliament and the highest political offices, there is a tendency to elect persons with longer previous parliamentary experience for the Office of Speaker, especially from long-established parties. However, the prestige and authority of Speaker often depends on subjective factors and concrete personality occupying the position. Not only the circumstances of the time but also the personality of the politician shape the role and tasks the Speaker performs. In view of the essential role of political leaders in the building of institutions, the analysis of a Speaker’s role in a new democracy seems to be especially meaningful, thus providing an important additional insight into the institutionalisation studies of legislatures.